Infecção pela Leishmania chagasi: papel dos receptores Toll-like 2 e 4 alterações genotóxicas em camundongos BALB/c - Cezário, Glaucia Aparecida Gomes [UNESP] (2011)
Toll-like receptors (TLRs) present in innate immune cells recognize pathogen molecules and influence on immunity to control the host-parasite interaction. Our objective was to evaluate the mRNA expression of TLR-2 and 4, expression and production of IL-12, IFN-γ, TNF-α, IL-17, IL-10 and TGF-β and NO production during infection with Leishmania chagasi and correlate TLR2 and 4 expressions with cytokines production and NO. Infection resulted in increased TLR2, TLR4, IL-17, TNF-α and TGF-β expression at the beginning of infection, with a decrease at the final phase in according the parasitic load; IFN- γ and IL-12 decreased at the peak of parasitemia and increased at the final phase; IL-10 increased during the whole period under analysis. With respect to cytokines and NO production, TGF-β, TNF-α and IL-17 showed high rates at the initial phase, and IFN-γ and IL-12 showed high rates at the final phase; IL-10 and NO showed increasing production during the infection period evaluated. There was a positive correlation of TLR2 and 4 with TNF-α, IL-17, NO, IL-10 and TGF-β at the beginning of infection, and with TNF-α, IL-17 and TGF-β at the end. Our data suggest that L. chagasi was in contact with host’s cells via TLR2 and 4, which resulted in cytokine modulation. This interaction could be considered as pathogenic mechanism in visceral leishmaniasis